The Association of Chronic Oral Mucositis with Quality of Life in Head and Neck Cancer Patients Undergoing Radiotherapy - Sadoughi, Hamid-Reza; Mahmoudi, Rahil; Radfar, Pouya; Baghani, Zahra; Assarzadeh, Hossein; Ghahramani-Asl, Ruhollah (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Oral mucositis is a common and debilitating side effect of radiotherapy in patients with head and neck cancer, significantly impacting their quality of life. This study aimed to investigate the prevalence of chronic oral mucositis and its association with the quality of life in patients undergoing head and neck radiotherapy. Materials and Methods: This descriptive-analytical study was conducted on patients with head and neck cancer receiving radiotherapy at Radiotherapy department of Vasei hospital, Sabzevar. Demographic data (age, gender, comorbidities, tobacco use, and medications) and clinical data (cancer type, radiation dose, and radiotherapy duration) were collected. Quality of life was assessed using the WHOQOL-BREF questionnaire, and the severity of oral mucositis was evaluated based on WHO criteria. Data were analyzed using descriptive and analytical statistical methods, including chi-square, independent t-tests, and Mann-Whitney tests. Results: Oral mucositis was observed in 90% of patients undergoing head and neck radiotherapy, with its severity significantly correlated with radiation dose (p < 0.001), radiotherapy duration (p = 0.02), and the presence of comorbidities (p = 0.03). Patients with chronic mucositis reported significantly different quality of life scores across physical, psychological, and social domains, with notable reductions in mental (p < 0.001), social (p < 0.001), and environmental health (p < 0.001). Additionally, tobacco use (CI: 1.3–6.1, p < 0.001) and a history of chemotherapy (CI: 1.1–5.2, p = 0.02) were associated with increased symptom severity. A significant correlation was observed between younger patient age and the occurrence of dysphagia and chronic mucositis (p < 0.001). Conclusion: Chronic oral mucositis is a prevalent complication in head and neck radiotherapy patients, adversely affecting their quality of life. Effective management through preventive and therapeutic strategies can enhance patient outcomes. Future studies with larger sample sizes and a focus on novel therapeutic interventions for mucositis are recommended.